2011
DOI: 10.1007/s00011-011-0384-8
|View full text |Cite
|
Sign up to set email alerts
|

C-peptide reduces pro-inflammatory cytokine secretion in LPS-stimulated U937 monocytes in condition of hyperglycemia

Abstract: We conclude that, in conditions of hyperglycemia, C-peptide reduces monocytes activation via inhibition of the NF-κB pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 44 publications
(62 reference statements)
2
38
0
Order By: Relevance
“…It was also observed that the shorter the interval between preceding infection and T1D diagnosis, the lower the release of C-peptide. It has recently been shown that monocytes represent an additional cellular target for C-peptide anti-inflammatory activity (24). Monocytes are pivotal cells in inflammatory responses as they serve as the principal reservoir of proinflammatory cytokines, e.g., TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that the shorter the interval between preceding infection and T1D diagnosis, the lower the release of C-peptide. It has recently been shown that monocytes represent an additional cellular target for C-peptide anti-inflammatory activity (24). Monocytes are pivotal cells in inflammatory responses as they serve as the principal reservoir of proinflammatory cytokines, e.g., TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibited cytokines include IL-6, IL-8, macrophage inflammatory protein- (MIP-) 1 α , MIP-1 β [17], TNF- α , and reactive oxygen species [18]. …”
Section: Hyperglycemia and Innate Immune Cellsmentioning
confidence: 99%
“…An investigation into insulin's and C-peptide's roles in modulation of human saphenous vein neointima formation revealed that C-peptide increased endothelial cell number by about 40%, thus indicating that C-peptide may promote re-endothelialization and thus limiting neointimal development (70). C-peptide has also been shown to reduce systemic inflammatory responses that are deleterious to the endothelium by lowering circulating levels of the proinflammatory cytokines IL-1, IL-6, macrophage inflammatory protein (MIP)-1␣, and TNF-␣, effects that most likely occur through inhibition of activated monocytes (11,34,108). Vascular smooth muscle cells are yet another cell type that plays a critical role in vascular disease and atherosclerotic plaque formation.…”
Section: E959 Physiology Of C-peptidementioning
confidence: 99%